Primary and secondary lymphomas of the breast: – analysis of the problem on the basis of two cases - Litwiniuk, Maria; Rożnowski, Krzysztof; Tomczak, Piotr (Contemporary Oncology/Współczesna Onkologia, 2004)
Primary lymphoma of the breast is a rare disease representing about 0.05-0.5% of breast tumours and 2% of extranodal non-Hodgkin’s lymphomas. Most primary breast lymphomas are high-grade or intermediate malignant neoplasms, mainly large B-cell and Burkitt type. Basic imaging tests like mammography or ultrasonography of the breast do not give specific findings: pathological mass without microcalcifications typical for breast cancer. Magnetic resonance scans give more information, especially about localisation and correlation of tumour to other breast’s structures. But for establishing a precise diagnosis it is necessary to perform a histopathological examination of specimens taken during core or excision biopsy, completed by immunochemistry staining. After establishing the diagnosis, as in other cases of lymphomas, a typical staging process must be done, including imaging tests of the chest, abdomen and pelvis, examination of bone marrow (both aspiration of bone marrow and trepanobiopsy) and sometimes computed tomography of the central nervous system with the examination of the cerebrospinal fluid. The treatment depends on the stage of the disease. In the case of isolated breast lymphomas the treatment consists of chemotherapy (usually started with CHOP schedule), followed by radical radiotherapy of the breast with or without irradiation of regional lymph nodes. Recurrences which are observed quite frequently create a great treatment problem especially when the central nervous system is involved. In this report we describe two cases of lymphomas of the breast: primary lymphoma of the breast and secondary involvement by Hodgkin’s disease.